e - Izharulhak Bin Saiful Hafni; Putri Hardiyanti; Faridl Hakim; Meor Muhammed Afique Meor Johari (MADINAH, 2025)
This article presents an in-depth study of the pedagogical methodology employed by Imam Burhanuddin al-Zarnuji in his seminal work, Ta'lim al-Muta'allim, with a particular focus on his strategic integration of poetic counsel. The analysis is conducted through the analytical framework of Albert Bandura’s Social Learning Theory. The findings indicate a profound and intuitive alignment between al-Zarnuji’s classical Islamic pedagogical approach and modern psychological principles. Specifically, the poetic verses within Ta'lim al-Muta'allim effectively embody principles of modeling, vicarious reinforcement, and self-efficacy. This demonstrates that al-Zarnuji’s methods, formulated centuries ago, possess a psychological depth that resonates with contemporary learning theories, positioning Arabic poetry as a strategic instrument for shaping the character and intellect of the learner. The article further discusses the contemporary relevance of these findings for character education and holistic Islamic education, while also acknowledging the necessity for critical engagement and future empirical research to fully operationalize these insights in modern educational contexts.